The Thrill of Speedy Descents: A Pilot Study on Differences in Facially Expressed Online Emotions and Retrospective Measures of Emotions During a Downhill Mountain-Bike Descent - Hetland, Audun; Kjelstrup, Eirik; Mittner, Matthias; Vittersø, Joar (Frontiers in Psychology, 2019)
When extreme sport athletes explain the engagement behind their taxing and risky endeavors, they often refer to the happiness generated by the activities. However, during the activity, these athletes seem neither pleased nor happy. This article proposes some answers from a study of facially-expressed emotions measured moment-by-moment during downhill mountain-biking. Self-reported emotions were also assessed immediately after the trip was over. The participants display less happiness during the activity as compared to before and after the activity. No significant associations between facially expressed and self-reported emotions were observed. Findings are discussed with reference to the Functional Well-being Approach arguing that some momentary feelings are non-evaluative in the sense of being caused by the difficulty of the ongoing activity. Within this framework, easy tasks produce happy feelings while difficult tasks produce interest—regardless of whether a goal has been reached or not. In contrast, retrospective emotions involve the evaluation of the activity in relation to its goal. When a goal is accomplished, the accompanying feelings is positive. If a goal (or value) is threatened, lost or not achieved, negative feelings follow.